Different Techniques for Measuring Spatial Sound Properties of Auditoria: a Review. (October 2020) - Bevilacqua, A; Merli, F
Abstract: The interest in sound spatialization is strongly increased throughout the last decade. Sound spatialization, or as it is commonly named auralization, is very important for both the design phase of any listening room and the virtual reproduction of a 3D sound field [1]. The international standard ISO 3382:2009 explains the different techniques of how to measure spatial parameters (e.g. LE, LF, IACC) and one of the methods that can be performed for a binaural measurement is the utilization of a dummy head. Nowadays room impulse response (RIR) is often measured by using multichannel transducers working independently each other. This technique is very useful to virtually reproduce a 3D soundscape, corresponding to the same sound perception as it is found inside the architectural volume where the measurements have been performed [2]. In this paper, an alternative procedure of measuring and reconstructing the auralization characteristics is presented. Furthermore, this methodology has been compared with other techniques of 3D sound reproduction. This paper treats the opportunity to improve the quality of soundscape reproduction other than the analysis of acoustical parameters required by standards.